Spatial approach of leprosy in the State of São Paulo, 2009-2012 - Flávia Regina Ferreira; Luiz Fernando Costa Nascimento (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Background: Leprosy is a chronic, infectious disease that affects the skin and the peripheral nervous system and can lead to permanent disability and/or deformity. Objectives: To identify the distribution and to quantify the spatial dependence of the detection rates of new cases of Hansen's disease in the State of São Paulo, correlating with socioeconomic variables. Methods: Ecological and exploratory study with data on the detection rates of new cases of Hansen's disease among residents of São Paulo State municipalities between 2009-2012. The average rate per 10,0000 inhabitants was estimated. Information on the proportion of the population with low-income and the values of the Gini index were obtained. Thematic maps were constructed with the average rates and with those obtained by the Bayesian estimator; Moran and Kernel maps were also constructed. Spatial analysis by TerraView program. An alpha of 5% was adopted. Results: In total, 7163 new cases of Hansen's disease were recorded throughout the state. The average rate per 10,000 inhabitants, was 0.71 (SD = 1.06), ranging from zero to 12.87, with higher rates in the west of the State, in the metropolitan area of the capital and the Paraiba Valley. Municipalities with high priority for intervention were located in the west and northwest of the State. There was no correlation between rates with Gini index and low income. Study limitations: Possible inconsistency of Hansen's disease notification database regarding information quantity, quality and processing. Conclusions: This study identified the distribution and quantified the spatial dependence of the detection rates of new cases of Hansen's disease in the State of São Paulo, corroborating previous studies and serving as a subsidy to health managers.